Novel eco-friendly design and fabrication: Application of low-cost, smokeless, mobile charcoal furnace and wood vinegar products for aging society - Samseemoung, Grianggai; Suwan, Pimsiree; Tuenpusa, Pongpith; Hongthong, Chairat; O-Charoen, Narongchai; Samseemung, Malarin (Agriculture and Natural Resources, 2024)
Importance of the work: A low-cost, smokeless, mobile charcoal furnace with a wood vinegar product condensing system was fabricated. It is environmentally friendly and suitable for the elderly. The developed furnace can increase productivity compared to existing conventional units and can be operated easily by the elderly to generate charcoal for income. Objectives: To develop and evaluate a portable, smokeless charcoal furnace equipped with a wood vinegar condensation system to enhance the efficiency of charcoal production, reduce the required production time, and improve the quality of the charcoal produced. Additionally, the study also analyzes its economic viability. Materials & Methods: The production of charcoal involved exposing bamboo and Acacia auriculiformis wood to 200°C, 250°C or 300°C for 5 hr, 6 hr or 8 hr. The quality of the resulting charcoal was determined based on several factors: heating value, weight, yield, moisture content and the amount of wood vinegar generated. Results: The charcoal furnace system had the highest capacity, producing 7 kg/hr of charcoal. It took 5 hr to complete the burning process and an additional 15 min to remove the charcoal. Engineering economic analysis was used to determine the viability of using the portable, smokeless charcoal furnace. It was determined that the cost of production was USD 0.18 /kg. The break-even point for this operation was 12 hr/yr and the payback period was 0.021 yr. Main finding: The charcoal kiln system could be moved to different locations and was suitable for elderly workers. The quality of charcoal products was higher than the products available on the market and their value was increased by adding a wood vinegar condensation system.